Problematika Hukum Penerbitan Surat Keterangan Tanah Terhadap Kepastian Hukum Hak Atas Tanah - Tajarudin Tajarudin; Kms. Novyar Satriawan Fikri; Bambang Sasmita Adi Putra (MAN 4 Kota Pekanbaru, 2026)
Land is a strategic resource whose governance must ensure legal certainty for right holders. Although Indonesia's land registration system is regulated under the Basic Agrarian Law and Government Regulation Number 24 of 1997, many rural communities still rely on the Surat Keterangan Tanah (Land Statement Letter) as preliminary evidence of land possession before formal certification. This study analyzes its legal status, the juridical issues surrounding its issuance, and its role in providing legal certainty. Using a normative juridical method with statutory and conceptual approaches, the research finds that the Land Statement Letter serves only as preliminary evidence of physical possession rather than conclusive proof of ownership. Its legal effectiveness is weakened by inadequate verification of land history, limited application of the publicity principle, regulatory inconsistencies, and incomplete implementation of the Complete Systematic Land Registration program. The study concludes that legal certainty based on this document remains temporary and should be strengthened through formal land registration, regulatory harmonization, reinforcement of rechtsverwerking, and improved village-level land administration.